The ethnic density effect on alcohol use among ethnic minority people in the UK - Bécares, Laia (Journal of epidemiology and community health, 2011)
Despite lower alcohol drinking rates of UK ethnic minority people (excluding Irish) compared with those of the white majority, events of racial discrimination expose ethnic minorities to unique stressors that elevate the risk for escapist drinking. Studies of ethnic density, the geographical concentration of ethnic minorities in an area, have found racism to be less prevalent in areas of increased ethnic density, and this study hypothesises that ethnic minority people living in areas of high ethnic density will report less alcohol use relative to their counterparts, due to decreased experienced racism and increased sociocultural norms.